2012
DOI: 10.1177/1933719111432872
|View full text |Cite
|
Sign up to set email alerts
|

Variants in Follicle-Stimulating Hormone Receptor Gene in Infertile Brazilian Men and the Correlation to FSH Serum Levels and Sperm Count

Abstract: The aim of the study was to analyze the distribution of the follicle-stimulating hormone (FSH) receptor (FSHR) Ala307Thr and Asn680Ser polymorphisms in infertile Brazilian men and evaluate the possible role of these polymorphisms on the serum levels of FSH and in sperm count. A case-control study was performed comprising138 infertile men with nonobstructive azoospermia (n = 53) or severe oligozoospermia (n = 85), and 217 fertile men as controls. Genotyping of FSHR polymorphisms was performed by real-time polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…At present, the association between FSHR gene polymorphisms and the risk of male infertility has been reported both in China and abroad, the conclusions from these studies have been inconsistent. Some studies have reported no significant association between the FSHR gene Thr307Ala and Asn680Ser polymorphisms and male infertility, and found that these polymorphisms also had no effect on serum FSH level or semen quality (Ghirelli-Filho et al, 2012). However, Shimoda et al (2009) and Safarinejad et al (2011) reported that the combination genotypes Thr/Ala-Ser/Asn increased the risk of male infertility.…”
Section: Discussionmentioning
confidence: 94%
“…At present, the association between FSHR gene polymorphisms and the risk of male infertility has been reported both in China and abroad, the conclusions from these studies have been inconsistent. Some studies have reported no significant association between the FSHR gene Thr307Ala and Asn680Ser polymorphisms and male infertility, and found that these polymorphisms also had no effect on serum FSH level or semen quality (Ghirelli-Filho et al, 2012). However, Shimoda et al (2009) and Safarinejad et al (2011) reported that the combination genotypes Thr/Ala-Ser/Asn increased the risk of male infertility.…”
Section: Discussionmentioning
confidence: 94%
“…A total of 15 studies, 4 studies from Asian population [ 24 , 28 30 ] and 11 studies from non-Asian population [ 1 , 13 , 14 , 16 , 17 , 22 , 31 35 ], met the inclusion criteria (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide, approximately 15% of couples cannot have a child, and in half of the cases the reason is the result of male infertility [ 1 ], which is a complex disorder caused by genetic, developmental, endocrine, or environmental factors or still unknown etiology [ 2 ]. It has been demonstrated that approximately 30% of infertility cases could be attributed to genetic defects, such as Klinefelter syndrome (KS), disorders of sexual development (DSD), or congenital absence of the vas deferens.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies reported no significant correlation among serum FSH levels, semen characteristics or fertility status and FSHR gene polymorphisms [7,10,14,22]. However, the hypothesis that the combination of heterozygous FSHR (codon 307 and 607) can be responsible for male infertility was reported by Shimoda et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…There are three common FSHR gene polymorphisms: one in the promoter region (at nucleotide position 29) and two in exon 10 [6]; the first SNP in exon 10 is located in the extracellular domain at position 307 (nucleotide 919) which can be occupied either by alanine (Ala) or by threonine (Thr), the second is located in the intracellular domain at position 680 (nucleotide 2039) and has either asparagine (Asn) or serine (Ser). A decrease in testicular FSHR binding ability has been reported in infertile men, but investigations on the distribution of the above mentioned variants gave conflicting results [7], showing the importance of ethnic differences [8][9][10]. Although no significant correlation between serum FSH levels and semen characteristics and FSHR gene polymorphisms was found, in some studies the combination of heterozygous Thr/Ala + Asn/Ser genotypes has been shown to increase the risk of male infertility [7,11,12].…”
Section: Introductionmentioning
confidence: 99%